Contributions to Loss Across the Magnetopause During an Electron Dropout Event. Issue 10 (8th October 2022) - George, H.; Reeves, G.; Cunningham, G.; Kalliokoski, M. M. H.; Kilpua, E.; Osmane, A.; Henderson, M. G.; Morley, S. K.; Hoilijoki, S.; Palmroth, M.
Abstract: Dropout events are dramatic decreases in radiation belt electron populations that can occur in as little as 30 minutes. Loss to magnetopause due to a combination of magnetopause shadowing and outward radial transport plays a significant role in these events. We examine the dropout of relativistic electron populations during the October 2012 geomagnetic storm using simulated electron phase space density, evaluating the contribution of different processes to losses across the magnetopause. We compare loss contribution from outward transport calculated using a standard empirical radial diffusion model that assumes a dipolar geomagnetic field to an event‐specific radial diffusion model evaluated with a non‐dipolar geomagnetic field. We additionally evaluate the contribution of Shabansky type 1 particles, which bounce along magnetic field lines with local equatorial maxima, to the loss calculated during this event. We find that the empirical radial diffusion model with a dipolar background field underestimates the contribution of radial diffusion to this dropout event by up to 10% when compared to the event‐specific, non‐dipolar radial diffusion model. We additionally find that including Shabansky type 1 particles in the initial electron phase space density, that is, allowing some magnetic field lines distorted from the typical single‐minima configuration in drift shell construction, increases the calculated loss by an average of 0.75%. This shows that the treatment of the geomagnetic field significantly impacts the calculation of electron losses to the magnetopause during dropout events, with the non‐dipolar treatment of radial diffusion being essential to accurately quantify the loss of outer radiation belt populations. Key Points: Geomagnetic field treatment greatly affects loss quantification during dropout events Non‐dipolar radial diffusion models are required to precisely quantify loss across the magnetopause Shabansky particles may significantly contribute to total loss across the magnetopause